Management Of Sustainable Business Development In Eu Countries - Ogunrinde, Opeyemi Hammed (“KROK” University, 2021)
The factors influencing business growth were studied using a quantitative method in this empirical research. The study is focused on primary data obtained on a convenience basis from various companies operating in various sectors in EU countries. Compensation policy, decentralisation, knowledge sharing, selective recruiting, and training and development are the independent variables. Since the findings are important, all of the hypotheses are endorsed. The reliability test, correlation, and regression analysis are used to analyse primary data. The study's results would be beneficial to companies operating in Economic Union EU countries, allowing them to develop and gain a competitive edge in the market. The study's conclusions and findings can be applied to all countries in the European Union